(3Mbhb GdEfSGf aj GdELQGAGJ GdLfGFjI (B:s (3OQGSI ebGQfI aj GdJTQjYGJ GdYQHjI hGdCLfHjI (B/s - (3CHh GdYfjf, CMeOs ((3GdEScfOQjI, eUQ (B:s (3ecJHI GdhaGA GdbGfhfjI,s, 2017)
(3JQJHW Mbhb GdeJge HMbhb GdEfSGf GQJHGW GdaQY HCUdg hGdLRA Hcdg, hPdc HGYJHGQ Mbhb GdeJge djSJ aj MbjbJgG EdG JWHjb NGU dMbhb GdEfSGf HUaI YGeI(B. (3hjYJHQ GQJHGW Mbhb GdeJge HMbhb GdEfSGf eSCdI efWbjI ddZGjI JHQQgG XQha GdhGbY hebJVjGJ GdbGfhf aj GdhbJ PGJg hJJeKd Jdc GdXQha aj Cf GdeJge aj cGaI eQGMd GdOYhi GdLfGFjI hMJi JeGe JfajP GdYbhHI jfXQ Edjg Hd hjLH GdMQU Ydi Pdc hJCcjOg HGYJHGQg eGRGd EfSGfG ChdG hHGdOQLI GdChdi(B.s
(3HHdjhLQGajI (B: (3UaMI (B715-797.s
Keywords: (3Mbhb GdEfSGfs -- (3bhGfjf hJTQjYGJs -- (3GdHdGO GdYQHjIs; (3bGfhf GdELQGAGJ GdLfGFjIs -- (3GdHdGO GdYQHjIs